Efforts to Build Employee Loyalty of E-Commerce Companies - Herminda, Herminda; Reinita Hadari, Ita; Muksin, Abdullah (Dinasti International Journal of Management Science, 2024)
The loyalty of employees  of E-commerce companies  needs to be questioned, given the difference in compensation and welfare received from their companies. This problem is interesting to examine, so that it is known which variables are able to build  E-commerce employee loyalty, for example the variables of Work Stress, work communication, compensation and job satisfaction. The population in this study, employees of E-Commerce Companies  in Jakarta, were selected by researchers, with a random sampling technique  obtained by 99 employees as respondents.  Data processing and analysis as well as hypothesis testing using SmartPLS program version 4. The results of the study found that the direct influence, variables of work stress, work communication, compensation significantly on job satisfaction. However, the variables of work stress and work communication do not have a direct effect on employee loyalty, while the variables of compensation and job satisfaction have a direct effect on employee loyalty of E-commerce Companies. The variable of job satisfaction is not able to play a role in mediating the variables of work stress and work communication because  the effect size is very low. In contrast to the job satisfaction variable which is able to mediate the compensation variable for employee loyalty of E-commerce Companies  because  the effect size is low to medium or medium. To increase employee loyalty, it is necessary to improve work communication, reduce work stress and ensure the maintenance of compensation received, so that employees feel they have high job satisfaction.